2021
DOI: 10.25115/psye.v13i2.3663
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards people with mental illness among medical students: A qualitative research

Abstract: Psychiatric illnesses affect more than 450 million people worldwide, with several consequences for those who are affected, along with the presence of high numbers of discrimination, stigmatization, and negative attitudes of the general population. These negative attitudes have been observed even in health professionals, negatively impacting on the quality of care, adherence to treatment and well-being of affected users. This study describes attitudes of medical students towards people with psychiatric illness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…As stigma is a complex social phenomenon transversally present in the society [ 1 - 6 ], innovative interventions involving use of technologies can be an effective tool for its reduction. However, one challenge in the implementation of this type of intervention is its adaptability to different contexts and countries, and so future interventions should include cross-cultural comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stigma is a complex social phenomenon transversally present in the society [ 1 - 6 ], innovative interventions involving use of technologies can be an effective tool for its reduction. However, one challenge in the implementation of this type of intervention is its adaptability to different contexts and countries, and so future interventions should include cross-cultural comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, discrimination, prejudice, and stereotypes present in society not only severely impact the recovery process, quality of life, and well-being of people with mental illnesses and their families, but also represent the main gap in accessing specialized mental health services by the general population [ 4 , 5 ]. The aforesaid has great relevance in the global context, where research has shown the presence of high levels of discrimination, stigma, and prejudice toward those impacted by mental health problems, especially schizophrenia and bipolar disorder [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As stigma is a complex social phenomenon transversally present in the society [1][2][3][4][5][6], innovative interventions involving use of technologies can be an effective tool for its reduction. However, one challenge in the implementation of this type of intervention is its adaptability to different contexts and countries, and so future interventions should include cross-cultural comparison.…”
Section: Future Researchmentioning
confidence: 99%
“…Romero et al (2019) mentioned that mental health professionals showed a positive attitude toward mental illness but also a relative support to coercive treatments. There are differences in attitudes modulated by professional category and setting (Rivas, 2021). Negative perspectives of nurses towards mental illnesses have been documented in multiple nations (Natalia, 2019;Koutra, 2022;Balasubramanian et al, 2023;Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%